Pengaruh eWOM, Brand Image, dan Kepuasan Pelanggan terhadap Keputusan Pembelian Produk di Eiger Kota Pasuruan - Wulan Nikmatur Rizkiyah; Dwita Laksmita Rachmawati; M. Tahajjudi Ghifary (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of electronic word of mouth (eWOM), brand image, and customer satisfaction on purchase decisions of Eiger products in Pasuruan City. Generation Z, as Eiger's primary target, tends to trust recommendations conveyed through eWOM on social media more than conventional promotions. Eiger once faced controversy over an approach deemed rigid and outdated in responding to public reviews. This approach drew criticism for being considered inconsistent with the evolution of social media and current consumer expectations. Data were collected through a survey using questionnaires from 65 respondents who are consumers of Eiger in Pasuruan City. Data analysis was conducted using multiple linear regression to identify the influence of independent variables on the dependent variable. The results indicate that eWOM, brand image, and customer satisfaction have a positive and significant impact on purchase decisions. This study emphasizes the importance for companies to enhance digital marketing activities, build a strong brand image, and maintain customer satisfaction to strengthen competitiveness in the market.